An Analysis of Inflectional Morphemes in a Short Story “The Child’s Story” by Charles Dickens - Ifadloh, Nur; Najerin, Muhammad Rizky; Nufus, Zahratun; Ulum, Miftakhul (STAIN Sultan Abdurrahman Kepulauan Riau, 2022)
This study aims to determine the inflectional morpheme contained in the short story entitled